(untitled) (Altre Modernità, 2016)
At present, the hegemony of neoliberal and neoconservative thought extends its utilitarian and commercial dominance over the state and on the daily lives of people, affecting their work, their relationships and their subjectivity, which implies greater job insecurity, relations little stable, fragile social institutions and labile subjectivities. With this social imagination the possibilities for future social projects, the inherent ability to instituting democratic nature, weakens. However, the new social movements, through a reflexive praxis based on cooperation and social action, seek to recover and conquer public spaces, politicized social aspects, and exercising active citizenship. Public School, though impregnated by hegemonic powers, is an autonomous field. If it stands as public space and as an ethical-political community, can promote autonomous social movements, instituting capacity, in order that future citizens can build their own future. Two specific cases that serve as examples: School garden as praxis which articulate social movement imaginary with School; and the parent of students movement for a public school. In both cases, put in play contexts, relationships and forms of learning that allow a pedagogy of social creation.